Predicting the probability of survival in acute paraquat poisoning - In O Sun; Sung Hye Shin; Hyun Ju Yoon; Kwang Young Lee (The Korean Society of Nephrology, 2016)
Background: Paraquat (PQ) concentration-time data have been used to predict prognosis for 3 decades. The aim of this study was to find a more accurate method to predict the probability of survival. Methods: This study included 788 patients with PQ poisoning who were diagnosed using plasma PQ concentration between January 2005 and August 2012. We divided these patients into 2 groups (survivors vs. nonsurvivors), compared their clinical characteristics, and analyzed the predictors of survival. Results: The mean age of the included patients was 57 years (range, 14-95 years). When we compared clinical characteristics between survivors (n = 149, 19%) and nonsurvivors (n = 639, 81%), survivors were younger (47 ± 14 years vs. 59 ± 16 years) and had lower plasma PQ concentrations (1.44 ± 8.77 μg/mL vs. 80.33 ± 123.15 μg/mL) than nonsurvivors. On admission, serum creatinine was lower in survivors than in nonsurvivors (0.95 ± 0.91 mg/dL vs. 1.88 ± 1.27 mg/dL). In multivariate logistic regression analysis, age and logarithmically converted serum creatinine [ln(Cr)], [ln(time)], and [ln(PQ)] were assessed as prognostic factors to predict survival in PQ poisoning. The predicted probability of survival using significant prognostic factors was exp (logit)/[1 + exp(logit)], where logit = -1.347 + [0.212 × sex (male = 1, female = 0)] + (0.032 × age) + [1.551 × ln(Cr)] + [0.391 × ln(hours since ingestion)] + [1.076 × ln(plasma PQ μg/mL)]. With this equation, the sensitivity and specificity were 86.5% and 98.7%, respectively. Conclusion: Age, ln(Cr), ln(time), and ln(PQ) were important prognostic factors in PQ poisoning, and our equation can be helpful to predict the survival in acute PQ poisoning patients.